Análisis biomecánico del pie protésico Bioc-dm2 - Martin, Jhon Hernandez (Universidad Tecnológica de Panamá, Panamá, 2019)
Walking is one of the aspects directly compromising human wellbeing, as it has a physical and emotional impact in daily life.For this study, we delve into the challenge of improving some walking conditions in a patient suffering lower limb loss, specifically at transtibialor transfemoral levels. Given that our purpose was the analysis, design and manufacture of a lower-limb prosthetic component, which fills the needsfor functionality, it became necessary to build a foot with all the quality standards associated to each and all movements required to form thecomplex fundamental pattern of walking. Besides, this foot should also easily endure weight, daily use and physical characteristics of the patientobject of this study. When performing physical validation and during human walk, a proper response is observed in terms of mechanics, materialsand dynamics of the component, thus making evident proper construction and assembly. On the other hand, it is feasible that design and verificationof the component provided a competitive element, as compared to existing elements currently in the market. The previous situation generated theneed for verification from the National Institute for Medications and Food (INVIMA), as well as the revision of the use replying device, forcomponent verification, in accordance with ISO 10328.